Money Demand and Inflation in Dollarized Economies : The Case of Russia - Ohnsorge, Franziska; Oomes, Nienke (Washington, D.C. : International Monetary Fund, 2005)
Money demand in dollarized economies often appears to be highly unstable, making it difficult to forecast and control inflation. In this paper, we show that a stable money demand function for Russia can be found for "effective broad money," which includes an estimate of foreign cash holdings. Moreover, we find that an excess supply of effective broad money is inflationary, while other excess money measures are not, and that effective broad money growth has the strongest and most persistent effect on short-run inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet